Transcriptome and metabolite conjoint analysis reveals the seed dormancy release process of perilla - He Wen; Sen Yang; Zhiwei Shang; Shimei Yang; Xingyue Li; Shunbo Yu; Heng Zhang; Ping Guo (Scientific Reports)
Abstract Seed dormancy is a common physiological phenomenon during storage which has a great impact on timely germination of seeds. An in-depth analysis of the physiological and molecular mechanisms of perilla seed dormancy release is of great significance for cultivating high-vigor perilla varieties. We used gibberellin A3-soaked seeds (GA), natural dormancy-release seeds (CK) and water-soaked seeds (WA) to study the changes in the transcriptome and metabolome of dormancy release. The germination test revealed that the optimum concentration of gibberellin A3 for releasing dormancy from perilla seeds was 200 mg/L. The results revealed that plant hormone signal transduction, starch and sucrose metabolism and citric acid cycle were significantly enriched metabolic pathways closely related to seed dormancy release. Perilla seeds release their dormancy by enhancing the expression of GID1, PIF3, SnRK2, IAA, ARR-A, GH3, MKK4_5, otsB, GN1_2_3, glgC, WAXY, inhibiting the expression of DELLA, PP2C, glga, bglX, and GN4, and regulating the content of gibberellin A4, abscisic acid, auxin, sucrose, maltose, trehalose, and α-D-glucose 1-phosphate. Auxin plays an important role in breaking perilla seed dormancy and promoting seed germination. The energy required for breaking seed dormancy and germination of perilla seeds is mainly provided through sucrose metabolism. Citric acid cycle (TCA cycle) is the main energy supply transformation pathway for seed germination.